Service Quality, Tourist Satisfaction, and Revisit Intention: Empirical Evidence from Emerging Destinations - Karyono Karyono; Deo Renaldi Saputra; Sugianto Sugianto; Fendy Prasetyawan (Journal of Management, Entrepreneurship, and Tourism, 2026)
The increasing competitiveness of global tourism markets has intensified the strategic importance of understanding the behavioral mechanisms that encourage tourists to revisit destinations, particularly in emerging tourism contexts characterized by uneven service standards and dynamic visitor expectations. This study investigates the interrelationships between service quality, tourist satisfaction, and revisit intention, aiming to clarify their causal structure within emerging destinations. Employing an empirical, quantitative research design, data were collected from domestic and international tourists who had visited selected emerging destinations within the previous twelve months. Using a structured questionnaire and purposive sampling, the study analyzed responses through structural equation modeling to test both direct and mediated effects among the key constructs. The results demonstrate that service quality significantly influences tourist satisfaction, while tourist satisfaction exerts a strong and positive effect on revisit intention. Furthermore, tourist satisfaction partially mediates the relationship between service quality and revisit intention, with the indirect effect exceeding the direct effect. These findings indicate that revisit intention is primarily shaped through tourists’ post-consumption evaluative processes rather than service performance alone. The study contributes theoretically by refining the service quality–satisfaction–loyalty framework in emerging destination settings and offers practical insights for destination managers seeking sustainable competitiveness through satisfaction-oriented service strategies.